Twisting the truth: Foundations of wishful thinking - Matthew Kovach (Theoretical Economics, 2020)
Considerable evidence shows that people have optimistic beliefs about future outcomes. I present an axiomatic model of wishful thinking (WT), in which an endowed alternative, or status quo, influences the agent's beliefs over states and thus induces such optimism. I introduce a behavioral axiom formalizing WT and derive a representation in which the agent overweights states in which the endowment provides a higher payoff. WT is a novel channel through which an endowment may influence choice behavior and provides a coherent explanation for a variety of observed behavior, including choice reversals among non-status quo alternatives when the status quo changes. WT leads to inefficient risk sharing in an exchange economy and has unique implications for the gap between willingness to accept and willingness to pay for endowed goods.
Keywords: D01; D11; D80; D81; D83; 330; Wishful thinking; status quo bias; reference dependence; belief distortions; optimism